2001
DOI: 10.1002/mc.1035
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Transcription Factor HNF3γ in the Effect of o‐Aminoazotoluene on Glucocorticoid Induction of Tyrosine Aminotransferase in Mice Sensitive to its Hepatocarcinogenic Action

Abstract: In the rodent liver, hepatocarcinogens inhibit the glucocorticoid induction of several liver-specific genes, including tyrosine aminotransferase (TAT). A distinct positive correlation exists in mice between the extent of inhibition of TAT induction after acute administration of o-aminoazotoluene (OAT) and the frequency of liver tumors after chronic exposure to the carcinogen. To elucidate the mechanism of the carcinogenic action, the effects of OAT on the DNA-binding activity of several transcription factors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…A relationship between glucocorticoid induction of TAT and DNA-binding activity of FOXA was revealed after administration of OAT to mice sensitive and resistant to the hepatocarcinogenic effect of this compound. OAT significantly decreased glucocorticoid induction of TAT and DNAbinding activity of FOXA in the liver of sensitive mice (A and SWR), but not in resistant animals (CC57BR and AKR) [4]. These data suggest that FOXA proteins determine the amplitude of glucocorticoid induction of TAT in mice (similarly to rats [8]).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A relationship between glucocorticoid induction of TAT and DNA-binding activity of FOXA was revealed after administration of OAT to mice sensitive and resistant to the hepatocarcinogenic effect of this compound. OAT significantly decreased glucocorticoid induction of TAT and DNAbinding activity of FOXA in the liver of sensitive mice (A and SWR), but not in resistant animals (CC57BR and AKR) [4]. These data suggest that FOXA proteins determine the amplitude of glucocorticoid induction of TAT in mice (similarly to rats [8]).…”
Section: Resultsmentioning
confidence: 82%
“…As differentiated from 3'-MeDAB, specific hepatocarcinogen OAT decreased DNA-binding activity of FOXA and glucocorticoid induction of TAT in SWR mice. Activity of other transcription factors involved in glucocorticoid induction of rat TAT gene (e.g., C/EBP and GME-binding proteins [2,7]) remained unchanged after administration of aminoazo dyes to mice or rats [4,6]. …”
mentioning
confidence: 99%
“…For example, 2'3-dimethyl-4-aminoazobenzene (oaminotoluene; OAT; CAS: 97-56-3) reduces DNAbinding activity of FoxA and attenuates glucocorticoid induction of TAT in sensitive mice more than 2-fold. Another azo compound, 3'-methyl-4-dimethylaminoazobenzene (3'MeDAB; CAS: 55-80-1), causes tumors in rats but not in adult mice [6,7]. This compound 2-fold reduces FoxA activity and level of glucocorticoid induction of TAT in rats, but does not change it in mice [6,7].…”
mentioning
confidence: 97%
“…Their products regulate cell differentiation and metabolism and maintain cell phenotype [3,5,8,9]. We studied the involvement of FoxA factors in tumor induction on the model of various hepatocarcinogenic substances, primarily azo compounds [6,7,11] characterized by pronounced tissue, species, and strain specifi city. It was found that the decrease in activities of FoxA proteins and attenuation of glucocorticoid induction of tyrosine aminotransferase (L-tyrosine:2-oxoglutarate aminotransferase; TAT) gene expressed exclusively in the liver take place only if the substance is hepatocarcinogenic for this rodent species, strain, or gender, but not in resistant animals.…”
mentioning
confidence: 99%
“…В предыдущих работах было показано, что под действием ОАТ происходит нарушение глюкокортикоидной регуляции специфического для печени фермента тирозинаминотрансферазы [10] и ДНК-связывающей активности транскрипционного фактора HNF3 [11] только у линий мышей, предрасположенных к его гепатоканцерогенному действию. Настоящее исследование выявило снижение экспрессии PPAR-a, PPAR-g, RXR-a и RXR-b в печени мышей линии DD, чувствительной к химическому гепатоканцерогенезу, которое могло быть следствием пониженной у них функции гипоталамо-гипофизарной системы.…”
unclassified